2016
DOI: 10.3109/02770903.2015.1064951
|View full text |Cite
|
Sign up to set email alerts
|

Toxocariasis and childhood asthma: A case-control study

Abstract: This study did not find a statistically significant association between seropositivity to Toxocara sp. and risk of asthma in children. Low family income, low paternal education level, concomitant allergic rhinitis, family history of asthma and allergic rhinitis and contact with cats were independent factors associated with childhood asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
(52 reference statements)
1
10
1
1
Order By: Relevance
“…A meta-analysis study including seven studies on children and three studies on adults involving a total of 1530 participants (723 cases of asthma and 807 controls) revealed a significant association between Toxocara seropositivity and asthma (OR: 3.36, 95% CI: 1.76 -6.42) (3). However, another study that was performed in Brazil with inclusion criteria similar to those used in our study did not find this association (18).…”
Section: Discussioncontrasting
confidence: 54%
“…A meta-analysis study including seven studies on children and three studies on adults involving a total of 1530 participants (723 cases of asthma and 807 controls) revealed a significant association between Toxocara seropositivity and asthma (OR: 3.36, 95% CI: 1.76 -6.42) (3). However, another study that was performed in Brazil with inclusion criteria similar to those used in our study did not find this association (18).…”
Section: Discussioncontrasting
confidence: 54%
“…Studies on Toxocara spp. seropositivity in the USA (Sharghi et al , 2001), Spain (Gonzalez-Quintela et al , 2006), Turkey (Kustimur et al , 2007), Sri Lanka (Fernando et al , 2009), Brazil (Cadore et al , 2016; Silva et al, 2017), and Norway (Jõgi et al , 2018) with clinical asthma showed no difference in Toxocara spp. infection between asthmatic and non-asthmatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The patient only showed marked improvement after treatment with thiabendazole. On the other hand, Grama et al 55 and Cadore et al 56 did not find an association between atopy and an increased risk of asthmatic manifestations in children with serological tests positive for anti- Toxocara antibodies. In 2012, Mendonça et al 51 did not find an association between positivity for aeroallergens and Toxocara infections in children living in poor areas of Salvador (Bahia State) and postulated that increased polyclonal IgE levels and the induction of a modified Th2 immune response to Toxocara infection might prevent the development of skin hypersensitivity to aeroallergens.…”
Section: Frequency and Characteristics Of Human Infections Due To Toxocaramentioning
confidence: 91%